From control orders to TPIMs: variations on a number of themes in British legal responses to terrorism - Hunt, Adrian (Crime, law and social change, 2014)
As part of its response to terrorism the British government has established and employed a number of specially created Executive powers as an alternative to prosecution. These powers facilitate the imposition of controls on individuals judged to be involved in terrorism who are thought to present a continuing danger. This article examines the latest version of these powers, "Terrorism Prevention and Implementation Measures", which replaced a regime of restrictions called "control orders". The Government argues that the new measures are an improvement on the control order system because they represent a fairer balance between the human rights and civil liberties of the individuals concerned, and the need to protect society from the danger these individuals are thought to present. However it is argued that this is an inaccurate picture of these new measures. Many of the key features of the control order regime remain, and some of the changes are cosmetic rather than real. Further, other features of the new regime were necessitated by case law concerning control orders and therefore do not really represent concessions to civil liberties on the Government’s part. It will also be shown that some of the changes serve as a basis for questioning the underlying justification for this sort of regime. In particular, the imposition of a time-limit on these measures means that individuals still judged to be a danger, will have to be subjected to ordinary criminal law powers of surveillance and investigation in any event.